Efficiently catching entangled microwave photons from a quantum transducer with shaped optical pumps - Changchun Zhong (Physical Review Research)
A quantum transducer, when working as a microwave and optical entanglement generator, provides a practical way to coherently connect optical communication channels and microwave quantum processors. Recent experiments on a quantum transducer verifying entanglement between the microwave and optical photons show the promise of approaching that goal. While flying optical photons can be efficiently controlled or detected, the microwave photon needs to be stored in a cavity or converted to the excitation of a superconducting qubit for further quantum operations. However, it remains challenging to efficiently capture or detect a single microwave photon with an arbitrary time profile. This work focuses on this challenge in the setting of an entanglement-based quantum transducer and proposes a solution by shaping the optical pump pulse. By Schmidt decomposing the output entangled state, we show that the microwave-optical photon pair takes a specific temporal profile that is controlled by the optical pump. The microwave photon from the transducer can be nearly perfectly absorbed by a receiving cavity with tunable coupling and is ready to be converted to the excitation of superconducting qubits, enabling further quantum operations.